Effects of concurrent response-independent reinforcement on fixed-interval schedule performance - Lattal, Kennon A. (1976)
In three experiments, behavior maintained by fixed-interval schedules changed when response-independent reinforcement was delivered concurrently according to fixed- or variable-time schedules. In Experiment I, a pattern of positively accelerated responding during fixed interval was changed to a linear pattern when response-independent reinforcement occurred under a variable-time schedule. Overall response rates (total responses/total time) decreased as the frequency of response-independent reinforcement increased. Experiment II showed that the response-rate changes in the first experiment were controlled by the response-reinforcer relation, but the changes in patterns of responding were similar whether concurrently available reinforcement at varying times was response-dependent or response-independent. In the final experiment, the addition of response-independent reinforcement at fixed times to a fixed-interval schedule resulted in changes in both local and overall response rates and in the occurrence of positively accelerated responding between reinforcements. These results suggest that the temporal distribution of reinforcers determines response patterns and that both the response-reinforcement dependency and the schedule of reinforcement determine overall response rates during concurrently scheduled response-dependent and response-independent reinforcement.